Role of indigenous knowledge and practices among the Bajau and Dusun communities towards biodiversity conservation in Kota Belud, Sabah, Malaysia - Adam, Anis Amalina (2021)
Indigenous knowledge of Bajau and Dusun people was developed from centuries of interacting, experimenting and adapting to the natural environment. Such knowledge was created as they historically inhabited biologically rich areas and ultimately dictated the way Bajau and Dusun people utilised the natural resources around them. Indigenous knowledge of Bajau and Dusun people is holistic and dynamic, emphasising the balance of physical and supernatural realms. Reflecting this concept to biodiversity conservation, indigenous knowledge of Bajau and Dusun people could be found in traditional medicine, river management, traditional hunting, and traditional farming. Thus, the unique knowledge of Bajau and Dusun people in various practices makes it important to study in the context of biodiversity conservation. This qualitative study applied case study approach to delve into the perspectives and experiences of Bajau and Dusun people regarding their indigenous knowledge system. The data in this study was collected through interviews, focus group discussion, and observation. Kota Belud in Sabah was selected as the study site and informants were chosen using purposive and snowball sampling techniques. The informants in this study were Dusuns and Bajaus, the two main ethnics in Kota Belud. Fieldworks for data collection involved 11 informants (n=11) all together. The data was analysed thematically with the aid of NVivo 8.The main findings in this study yielded three major themes reflecting the objectives. The first theme deals with indigenous knowledge and practices of Bajau and Dusun people in traditional farming, traditional hunting, river management, and traditional medicine. The second theme presents the initiatives of Bajau and Dusun people in transferring indigenous knowledge to their communities. The third theme touches on the documentation of indigenous knowledge of Bajau and Dusun people. Lastly, the findings of this study provide some implications to the body of knowledge by delivering discussions on the role of indigenous knowledge of Bajau and Dusun communities in biodiversity conservation. In practical, this study helps the government to strengthen the existing policies and create programmes pertaining to biodiversity conservation. This study also demonstrates significant implication from the perspectives of Bajau and Dusun communities with regards to indigenous knowledge documentation.